2020
DOI: 10.1016/j.ygyno.2020.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers in gynecologic oncology patients hospitalized with COVID-19 infection

Abstract: • Ferritin, procalcitonin, and CRP may have prognostic value for severe COVID-19 infection in gynecologic cancer patients. • Elevated admission white blood cell count, lactate, and creatinine may also be prognostic of severe COVID-19 disease. • D-dimer levels do not appear to be predictive of severe COVID-19 infection in patients with gynecologic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…33,34 A decision was taken to include the study with the later date of publication. 34 Twenty-eight studies were included for meta-analysis; these included patients from Asia (three studies), 29,35,36 the Americas (10 studies), 5,[37][38][39][40][41][42][43][44][45] Europe (13 studies), 9,34,[46][47][48][49][50][51][52][53][54][55][56] and multinational registries (two studies). 6,57 The 28 studies that reported mortality in cancer patients with COVID-19 admitted to the ICU included a total of 1,276 patients, with dates of recruitment ranging from January 23 to June 11, 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 A decision was taken to include the study with the later date of publication. 34 Twenty-eight studies were included for meta-analysis; these included patients from Asia (three studies), 29,35,36 the Americas (10 studies), 5,[37][38][39][40][41][42][43][44][45] Europe (13 studies), 9,34,[46][47][48][49][50][51][52][53][54][55][56] and multinational registries (two studies). 6,57 The 28 studies that reported mortality in cancer patients with COVID-19 admitted to the ICU included a total of 1,276 patients, with dates of recruitment ranging from January 23 to June 11, 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Fattizzo et al 47 Gonfiotti et al 48 Malard et al 51 Martin-Moro et al 49 Grasselli et al 34 Lee et al 46 Joharatnam-Hogan et al 52 Lamure et al 53 Shah et al 9 Passamonti et al 50 Haase et al 54 Garcia Suarez et al 55 Lievre et al 56 Subgroup Europe (I 2 = 51.61% , P = .016) Krause et al 42 Gupta et al 5 Robilotti et al 37 Mehta et al 38 Lara et al 39 Lunski et al 43 Luo et al 40 Singh et al 41 de Melo et al 45 Smith et al 44 Subgroup Americas (I 2 = 86.88% , P = .000)…”
Section: Studiesmentioning
confidence: 99%
“…[ 29 ] A multicenter retrospective study of 84 gynecological cancer patients found that CRP levels were significantly elevated in patients with severe infections (median 142.0 mg/L, IQR 62.4–217.1 vs median 62.3 mg/L, IQR 13.0–159.1; P = .02). [ 30 ] Most of these studies focused on Alpha strains. In this study, we did not analyze the association between CRP and severe pneumonia due to the low critical illness rate and mortality of Omicron.…”
Section: Discussionmentioning
confidence: 99%
“…With the spread and severity of the infection and the lack of control of virulence factors in the host, one of the main outcomes is the patient's death. (Upadhyay et al, 2020;Smith et al, 2020).…”
Section: Cytokine Stormmentioning
confidence: 99%
“…Individuals with more than one comorbidity tend to have a more severe prognosis and greater risk of death (Fakhroo et al, 2021). Despite all the studies related to the predictive role of biomarkers on poor prognosis in SARS-CoV-2 infection, it is known that, given the changes in the immune system and the inflammatory response of patients with chronic diseases, the association of biomarkers in this specific group is not fully elucidated, requiring further studies to understand the causal relationship entirely (Smith et al, 2020).…”
Section: Cytokine Stormmentioning
confidence: 99%